Potensi Gamifikasi Berbasis Platform Digital dalam Penelitian Pariwisata: Kajian Literatur - Gurning, Linda R M; Rahmanita, Myrza (STIEPAR YAPARI Bandung, 2023)
Gamification is an important theme of the future of tourism. Gamification in tourism is mostly applied to increase tourist attraction visits. Gamification is also applied for other purposes that can be used in supporting the tourism industry. Gamification in tourism uses digital video game platforms of Virtual Reality, Augmented Reality and Extended Reality. The boundaries between fantasy and reality become blurred in a digital platform-based game. This research aims to find out how the potential of digital platform-based gamification in the tourism industry through a literature review.This research uses a literature review of several previous studies in the period 2018 - 2023. The research method used is descriptive qualitative with the aim of gaining an in-depth understanding of the potential phenomenon of digital platform-based gamification in tourism research. The results show that the potential of digital platform-based gamification can be used to motivate tourists to be interested in destinations, increase customer satisfaction, increase brand awareness and loyalty, increase tourist visits, learn about amazing and historic places through mission completion, support tourism sustainable development goals, strengthen children to learn informally about tourism, and ultimately provide economic benefits to the community.